Investigation of fragmentation reactions of exotic nuclei in a high-energy approximation - Ismailova, A.N.; Janseitov, D.M.; Sharov, P.G. (Eurasian Journal of Physics and Functional Materials, 2026)
Studies of the properties of nuclei remote from the "valley of nuclear stability" make it possible to predict the properties of new nuclides based on systematic accumulations of data on the structure of nuclear matter. New phenomena in the behavior of nuclear matter are also being discovered. Such cores are called "exotic". The production of exotic nuclei is a multi-stage process, during which various approaches of theoretical and experimental physics are applied. One of the ways to obtain nuclei are fragmentation reactions of relatively light nuclei with high energy (more than 100 MeV), as a result of which exotic nuclei with different A and Z can be obtained. In this article, a study of the applicability of the high-energy approximation (HEA) in modeling such direct nuclear reactions was conducted and the results of comparing this approach with the exact solution of the Schrodinger equation using the example of a rectangular potential barrier and a Gaussian potential barrier are presented. Comparison of different approaches provides an understanding of the limitations of their applicability for further study of the properties of nuclei in interaction with each other and for solving the Schrodinger equation with similar potentials considered © 2022. Eurasian Journal of Physics and Functional Materials.All Rights Reserved. Recommended Citation Ismailova, A. N.; Janseitov, D. M.; and Sharov, P. G. (2022) "Investigation of fragmentation reactions of exotic nuclei in a high-energy approximation," Eurasian Journal of Physics and Functional Materials: Vol. 6: No. 2, Article 2. DOI: https://doi.org/10.32523/ejpfm.2022060202